Livelihood security in face of drought – Assessing the vulnerability of pastoral households. (January 2016) - Martin, Romina; Linstädter, Anja; Frank, Karin; Müller, Birgit
Abstract: Livestock grazing in drylands supports pastoral livelihoods but is facing multiple changes including shocks such as severe droughts. Herdsmen specifically cite drought events as a reason for the abandonment of their transhumance practices. The purpose of this study is to assess the relevance of drought as a driving force for losses of livelihood security leading to a specific systemic change – households abandoning transhumant pastoralism. We present and apply a framework for systematic analyses of the social–ecological functioning of pastoral resource use that consists of the following components: (1) A spatially-explicit social–ecological model for analyzing the system dynamics, especially in face of severe drought in connection with other driving forces of variability, (2) an operationalized measure for assessing livelihood security, and (3) a strategy for systematic vulnerability assessments of pastoral households by scenario comparison. This approach is applied to the land use system of the transhumant pastoralists in the High Atlas Mountains of Morocco. The results indicate that drought is the main threat to livelihood security in only a few cases, eventually forcing households to abandon their transhumant lifestyle. Instead, other (endogenous and exogenous) sources of variability were found to be the main driving force for vulnerability, depending on the household characteristics such as income needs and the level of pastoral mobility. We discuss implications on the role of severe drought in connection with other processes of global change such as social change and land use change for livelihood security in pastoral systems. Moreover, on the basis of these findings, we discuss how the relevance of shocks as a driving force of systemic changes in coupled human-nature-systems may be adequately explored. These conclusions concern the interplay of exogenous and endogenous factors, and unintended side-effects of intended changes. Highlights: We simulate grazing management and assess households' livelihood security. We differentiate pastoral household types by their state of vulnerability. Drought is the main driver for pastoral households to exit in only a few cases. Resource-consumer interaction dominates over the effects of drought. Increasing income needs and less mobility threaten pastoral livelihood security.